Use Google MAPS Techniques to Restriction Real Estate Taxable Properties - د. عثمان نصر; عنايات على الخضر; د. الطيب السماني (White Nile Journal for Studies and Research, 2018)
The use of geographic information systems (GIS) techniques in the field of tax collection is a modern method. It provides great potential for tax assessments of various types, especially real estate tax, based on the Metadata and spatial data of real estate sites, for the purpose of assessing real estate taxable properties in a particular area. In this research, we aim to exploit the advantages of using Google Maps technology, which is a very important technology provided by GIS based on the web by helping to inventory and estimate the real estate tax by accessing the real estate sites in an ideal manner by clicking on the location of the estate in the map of Google We obtain all the real estate data from the owner of the real estate and the leaseholder of the real estate and know all the metadata of the real estate is a piece of land or apartment or house or other with the possibility to see all the real estate taxable and whether it was estimated or not and was paid the tax for the property during the specified year. In this research, a number of tools were used, including Google Maps technology and object oriented programming languages based on object representation. A database was also used to manage all relationships and interrelationships between MYSQL tables and all this integration led to the design of a system capable of helping to estimate and estimate the real estate tax more Accuracy. Keywords: Google Maps, GIS, Real Estate Tax, Real Estate, Web Information Systems.